Image findings of patients with H1N1 virus pneumonia and acute respiratory failure - Henzler, Thomas; Meyer, Mathias; Kalenka, Armin; Alb, Markus; Schmid-Bindert, Gerald; Bartling, Sönke; Schoepf, Joseph U.; Schönberg, Stefan; Fink, Christian (Academic radiology, 2010)
Rationale and Objectives - The aim of this study was to assess the findings of chest radiography and high-resolution computed tomography in patients requiring intensive care unit treatment for severe H1N1 virus pneumonia. - Materials and Methods - In 2009, 10 patients required treatment in an intensive care unit for confirmed H1N1 pneumonia. All patients underwent chest radiography and high-resolution computed tomography. All 10 patients required mechanical ventilation because of respiratory failure. Nine patients presented with severe acute respiratory distress syndrome, and one patient died. Four patients underwent extracorporeal membrane oxygenation (ECMO) therapy. The results of chest radiography and high-resolution computed tomographic scans of these patients were systematically analyzed. - Results - The mean age of all patients was 44.1 ± 12.3 years. All 10 patients showed abnormal results on chest radiography. The radiographic abnormalities were bilateral and multifocal in 10 patients. The predominant radiographic findings were consolidations (n = 9), ground-glass opacities (n = 8), and reticular opacities (n = 2). The most frequent computed tomographic findings at presentation consisted of bilateral ground-glass opacities (n = 9), pleural effusion (n = 9), areas of consolidation (n = 8), interstitial marking (n = 8), and crazy paving (n = 4). All patients undergoing ECMO therapy showed extensive bilateral ground-glass opacities, multifocal areas of consolidation, and crazy paving. Pleural effusion was present in three of four patients undergoing ECMO therapy. - Conclusion - Patients requiring treatment in an intensive care unit for severe H1N1 pneumonia are at high risk for developing acute respiratory distress syndrome and frequently require ECMO therapy.
Gesehen am 19.04.2023
Available online 10 May 2010